2003
DOI: 10.1007/s00216-003-2080-1
|View full text |Cite
|
Sign up to set email alerts
|

Cell spreading on quartz crystal microbalance elicits positive frequency shifts indicative of viscosity changes

Abstract: Cell attachment and spreading on solid surfaces was investigated with a home-made quartz crystal microbalance (QCM), which measures the frequency, the transient decay time constant and the maximal oscillation amplitude. Initial interactions of the adsorbing cells with the QCM mainly induced a decrease of the frequency, coincident with mass adsorption. After about 80 min, the frequency increased continuously and after several hours exceeded the initial frequency measured before cell adsorption. Phase contrast a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(19 citation statements)
references
References 61 publications
1
15
0
3
Order By: Relevance
“…During the last 30 min of the experiment the Df responses deviated from the viscoelastic behavior as the platelets exhibited a greater level of energy dissipation above the sensor surface. 42 The Df plot for platelets interacting with fibrinogen coated 21 nm silica surfaces was quite different compared to the Df plot for platelets interacting with planar silica [ Fig. Coupled with this was the development of the actin cytoskeleton as shown by the spread morphology of platelets adhered to this surface [ Fig.…”
Section: Platelet Adhesionmentioning
confidence: 99%
“…During the last 30 min of the experiment the Df responses deviated from the viscoelastic behavior as the platelets exhibited a greater level of energy dissipation above the sensor surface. 42 The Df plot for platelets interacting with fibrinogen coated 21 nm silica surfaces was quite different compared to the Df plot for platelets interacting with planar silica [ Fig. Coupled with this was the development of the actin cytoskeleton as shown by the spread morphology of platelets adhered to this surface [ Fig.…”
Section: Platelet Adhesionmentioning
confidence: 99%
“…Redepenning et al (1993) observed similar behavior for a single layer of osteoblasts using the Kanazawa equation (Kanazawa and Gordon, 1985). If these results are compared with the adhesion kinetics for other cellular lines one concludes that, in this case, the kinetics is very slow, since during the testing time there was no observed increase in the frequency due to stiffening of the attached cells (Galli Marxer et al, 2003).…”
Section: Resultsmentioning
confidence: 65%
“…It has been used for determining the kinetics of cell attachment and spreading Nimeri et al, 1998) and for monitoring the long term growth of cells (Otto et al, 1999;Reipa et al, 2006). More recently, the QCM has been applied to characterization of cell viscoelasticity (Alessandrini et al, 2006;Galli Marxer et al, 2003;Li et al, 2008;Marx et al, 2005;Pax et al, 2005;Voinova et al, 2004). When the instrument used has the capability for monitoring the change in dissipation factor as well as frequency, the technique is termed QCM-D (QCM with dissipation monitoring).…”
Section: Probing Mechanical Response Of Cells With Quartz Crystal Micmentioning
confidence: 99%